A new species of Portulaca (Portulacaceae) from the state of Guanajuato (Mexico) - Ocampo Acosta, Gilberto (Instituto de Ecología, A.C., 2002)
Portulaca guanajuatensis is described as a new species. It is only known from the type locality, in the municipality of Iturbide, state of Guanajuato, Mexico. It belongs to section Portulaca of subgenus Portulaca and is distinguished mainly by its perennial habit with napiform root as well as by its red style.